2012
DOI: 10.1139/y2012-121
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydroxystilbene glucoside improves the learning and memory of amyloid-β1–42-injected rats and may be connected to synaptic changes in the hippocampus

Abstract: The aim of this study was to evaluate the protective effects of 2,3,5,4'-tetrahydroxystilbene-2-O-β-D-glucoside (TSG), an active component extracted from Polygonum multiflorum, on learning/memory deficits in Alzheimer's disease (AD). We randomly divided 24 male Sprague-Dawley rats among 4 groups: (i) the sham-operated group (control); (ii) sham-operated group also treated with TSG (sham+TSG); (iii) beta amyloid treated group (Aβ); and (iv) Aβ treatment group also treated with TSG (Aβ+TSG). Rats in the Aβ and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 43 publications
1
42
0
1
Order By: Relevance
“…In addition, a recent study showed that 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucoside, an active component extracted from P. multiflorum, exerts anti-AD properties by protecting synaptic structure and function in Aβ42-injected rats. 43) Consistently, in the present study, we also found the neuroprotective effects of 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucoside, in our in vivo and in vitro systems. Neuroprotective effects of R. glutinosa have also been reported in several previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, a recent study showed that 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucoside, an active component extracted from P. multiflorum, exerts anti-AD properties by protecting synaptic structure and function in Aβ42-injected rats. 43) Consistently, in the present study, we also found the neuroprotective effects of 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucoside, in our in vivo and in vitro systems. Neuroprotective effects of R. glutinosa have also been reported in several previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…In the CNS, TSG has been reported to protect dopaminergic neurons against 1-methyl-4-phenylpyridinium (MPP + )-induced injuries [8] and reverse the Aβ 1-42 -induced down-regulation of N-methyl- D -aspartate 2B expression and impairment in learning and memory [9,10]. TSG also attenuates the injury of cortical neurons in cerebral ischemia models in vitro and in vivo [11].…”
Section: Introductionmentioning
confidence: 99%
“…10 Moreover, it has been reported that some of the components had beneficial effects on learning and memory ability. 11,12 This study was designed to investigate the effect of ZJD on learning and memory ability, monoamine neurotransmitters, and neurotrophic factors in aging rats. Our data indicated that ZJD treatment might act through regulating the levels of monoamine neurotransmitters and neurotrophic factors in the brain, which played a role in improving learning and memory ability in aging rats.…”
Section: Introductionmentioning
confidence: 99%